Study of uterine kinetics in nonpregnant women using cine‐mode magnetic resonance imaging - Nakashima, Akira (Reprod Med Biol, 2019)
PURPOSE: To evaluate the uterine kinetics in each phase of the menstrual cycle when observed in detail using cine‐mode magnetic resonance imaging (MRI) of sagittal and transverse plane images. METHODS: Seven volunteers with a history of multiple natural pregnancies and deliveries were enrolled from January 2017 to May 2017. The kinetic parameters (depth, frequency, and direction) of uterine muscle contractions were evaluated in cine‐mode MRI. RESULTS: Strong contractions from the uterine cornua to cervix were detected during menstruation. In the late follicular phase, the frequency of opposing contractions from the cervix and uterine cornua increased. Immediately before ovulation, contractions from the cervix reached the uterine fundus. After ovulation, opposing contractions returned. These contractions gradually decreased in the mid‐luteal phase, while fine contractions from the cervix to the middle of the uterine body were frequently observed until 7 days after ovulation. Few contractions were observed in the implantation phase. CONCLUSIONS: Our data suggest that the uterine kinetics change in each phase of the menstrual cycle in accordance with the purpose of the uterus in each phase. Further, cine‐mode MRI studies of each phase are needed to assess the relationships between uterine kinetics and infertility.